2014
DOI: 10.1002/mus.24297
|View full text |Cite
|
Sign up to set email alerts
|

Spinal nerve composition and innervation of the axillary nerve

Abstract: These findings may be helpful to diagnose damage to axillary nerve structures that occur in such injuries as humerus fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Kang et al (2014) studied the nerve composition and found that more than half of the cases originated from C5 and C6. Another study investigated the surrounding structure on quadrangular space, TM and deltoid muscles using metric methods.…”
Section: Discussionmentioning
confidence: 99%
“…Kang et al (2014) studied the nerve composition and found that more than half of the cases originated from C5 and C6. Another study investigated the surrounding structure on quadrangular space, TM and deltoid muscles using metric methods.…”
Section: Discussionmentioning
confidence: 99%
“…The axillary nerve originates from the anterior branches of the C5-C6 spinal nerves and contributions from C4 and C7 have been described (Hur et al, 2011). The frequency varies from 13.3 % to 48.8 % for C4 and in 20 % to 56.2 % of cases, the axillary nerve may present contribution from C7 (Kang et al, 2014;Lee et al, 2016), so a traumatic injury to one of these branches can also affect the trophism of the deltoid and teres minor muscles, as well as proprioception, because the glenohumeral joint has articular branches coming from the axillary nerve, mainly from C6 (Lee et al, 2016).…”
Section: Booksmentioning
confidence: 99%